Potensi Antimikroba Ekstrak Kurma Ajwa (Phoenix dactylifera L) dalam Menurunkan Jumlah Angka Kuman Pada Lalat Buah (Drosophila Melanogaster) Berdasarkan Analisis Probit - Muhammad Firdaus; Arif Sumantri; Yusuf Rahman; Zilhadia Zilhadia (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
Waste can attract fruit flies (Drosophila melanogaster), which have the potential to carry pathogenic microorganisms that may cause infections in humans. One preventive approach against infection is the utilization of Ajwa date (Phoenix dactylifera) extract, which contains flavonoids and antioxidants with natural antibacterial properties. This study aimed to analyse the potential of Ajwa date extract as an antimicrobial agent in reducing the number of microorganisms carried on the legs of fruit flies (Drosophila melanogaster) as a biological model. This study employed a simple experimental design using a posttest-only control group design, consisting of one control group and four treatment groups treated with Ajwa date extract concentrations of 40%, 50%, 60%, and 70% at exposure intervals of 1, 6, 12, 18, and 24 hours. The total microbial count was measured using the Pour Plate method on Plate Count Agar (PCA) medium. Data were analyzed using two-way ANOVA with interaction and probit analysis to determine the LC₅₀ and LT₅₀ value. The results showed significant differences in the mean total microbial count among extract concentrations (F = 160.120; p < 0.001) and exposure intervals (F = 25.049; p < 0.001). In addition, the interaction between extract concentration and exposure interval was also statistically significant (F = 4.231; p = 0.001). The LC₅₀ value of Ajwa date extract was 51.648%, while the LT₅₀ value was 14.308 minutes. The findings indicate that Ajwa date (*Phoenix dactylifera*) extract has potential as a natural antimicrobial agent in reducing microorganisms carried on the legs of fruit flies (*Drosophila melanogaster*). Therefore, it may be further developed as an environmentally friendly disinfectant for microbial contamination control.